Development of TiO2 and Au Nanocomposite Electrode as CEA Immunosensor Transducer. Issue 6 (15th April 2014) - Aslan, Sema; Anik, Ülkü; Merkoçi, Arben
Abstract A carbon paste electrode (CPE) was modified by titanium(IV) oxide microparticles and then gold nanoparticles were dispersed in chitosan and immobilized on the CPE surface. As result a nanostructure modified composite electrode was obtained. Carcinoembriyonic antigen (CEA) was chosen as model analyte and the developed electrode was used as CEA immunosensor transducer for the first time. Two linear ranges of 0.01–1 ng/mL and 1–20 ng/mL with corresponding correlation coefficients R2=0.986 and R2=0.990, were found respectively. The limit of detection of the developed immunosensor was calculated as 0.01 ng/mL with 2.8 % relative standard deviation (n=5). The developed system was applied for CEA detection in synthetically prepared serum sample and very promising recovery values were obtained.